Portrayal of Woman: Short Stories of Shashi Deshpande’S Novel: Challenging Patriarchal Norms: The Portrayal of Women in Shashi Deshpande's Short Stories (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The aim of writing thispaper is to highlight the theme of helplessness on the part of a woman. Whethershe is a mother, daughter, sister or wife, the society always desires that sheshould be docile, timid and submissive. Through Deshpane’s novels for they aretrying to highlight the change towards which our society is moving but stillmillions of miles need to be covered for this change to be visible. A majorpreoccupation in recent Indian Women’s writings has been a delineation of innerlife and subtle interpersonal relationship. In Indian culture and heritage,individualism, quest for identity, protests and concepts of rebelliousness haveoften remained alien ideas, as far as women were concerned. Women were notsupposed to raise voices for their rights, protest against injustice orquestion the already existing beliefs, customs, rituals and superstitions. Theyhave to merely exist subjected to the patriarchal system.